Radiation-Induced Cervical Spinal Cord Cavernoma Following Head and Neck Radiotherapy: Case Report - Al-Jehani, Hosam; Najjar, Ahmad; Barnawi, Abdulwahid; Shedid, Daniel (Journal of Neurological Surgery Reports, 2020)
Cavernous angiomas are congenital vascular malformations that affect the central nervous system. Reports implicated radiation therapy as a triggering factor for the formation of cavernomas but not in relation with head and neck radiation therapy. Radiation-induced cavernomas (RIC) should be considered in the differential diagnosis of focal neurological symptoms in any patient who has received previous cranial-spinal or head and neck radiotherapy.
Keywords: arteriovenous malformation; head and neck cancer; radiation induced cavernoma; spinal cord cavernous angiomas